Laboratory Evaluation of Botteled Drinking Water Collected from Basra City - Zahei, Angham O.; Al Chalabi, Ahmed S.; Aboud, Entisar M. (Iraqi Journal of Science, 2021)
Forty-four bottles of drinking water were collected from the local markets of Basra City and stored in the laboratory refrigerator at 4ºC until the physical, chemical and biological measurements were carried out. The results showed a discrepancy in the compatibility of the specifications written on the drinking water bottle label with the sample measurements as well as the variation in the results with the Iraqi standards for bottled water. The percentage of bottled water that is not safe for drinking was 88.5% of the total samples of the study. This value is high and an indication of lack of control over marketing from the imported or produced in the local labs, so it is a danger to the health of the consumer. Results showed that the PH ranged 6.5–8 and did not exceed the values on the information sheet of the potable drinking water as well as the TDS, chloride, magnesium; nitrate and potassium which were within the permissible limits. In addition, the results showed that calcium, total hardness, fluoride and bacterial growth values exceeded the permissible limits, and there are different significations between factors in samples.